Energy use, growth and survival of coral reef snapper larvae reared at elevated temperatures - Shannon J. McMahon; Philip L. Munday; Jennifer M. Donelson (Coral Reefs, 2023)
The success of individuals during the pelagic larval phase is critical to maintaining healthy and viable populations of coral reef fishes; however, it is also the most environmentally sensitive and energetically demanding life stage. Climate change is increasing the frequency and intensity of marine heatwaves, which could have significant effects on the development and survival of larval coral reef fishes. However, little is known about how the larvae of pelagic-spawning coral reef fishes will be affected due to the difficulty of spawning and rearing these species in captivity. In this study, we tested how elevated temperatures, similar to those occurring during a marine heatwave, affected the yolk utilization, growth, and survival of larval, Lutjanus carponotatus , a common mesopredatory fish on Indo-west Pacific coral reefs. Eggs and larvae were reared at a current-day average summer temperature (28.5 °C) and two elevated temperatures (30 °C and 31.5 °C) until 14 d post-hatch (dph). Larvae in the elevated temperatures depleted their yolk reserves 39% faster than at the control temperature. The standard length of larvae was 55% (30 °C) and 92% (31.5 °C) longer in the elevated temperature treatments than the control temperature at 14 dph. Conversely, survival of larvae was 54% (30 °C) and 68% (31.5 °C) lower at elevated temperatures compared with the control temperature. This study provides new insights as to how the early life stages of coral reef fishes could be affected by ocean warming and marine heatwaves, with implications for their population dynamics.

Life‐history constraints, short adult life span and reproductive strategies in coral reef gobies of the genus Trimma - Nisha C. Goldsworthy; Maya Srinivasan; Patrick Smallhorn‐West; Lit‐Chien Cheah; Philip L. Munday; Geoffrey P. Jones (Journal of Fish Biology, 2022)
Body size influences many life‐history traits, with small‐bodied animals tending to have short life spans, high mortality and greater reproductive effort early in life. In this study, the authors investigated the life‐history traits and reproductive strategies of three small‐bodied coral reef gobies of the genus Trimma : Trimma benjamini , Trimma capostriatum and Trimma yanoi . The authors found all Trimma species studied attained a small body size of T. benjamini individual and one T. yanoi individual had ovarian and testicular tissue active simultaneously. The results of this study highlight the life‐history challenges small CRFs face on their path to reproduction and reproductive strategies that could be beneficial in fishes with high and unpredictable mortality and short reproductive life spans.

Rapid evolution fuels transcriptional plasticity to ocean acidification - Jingliang Kang; Ivan Nagelkerken; Jodie L. Rummer; Riccardo Rodolfo‐Metalpa; Philip L. Munday; Timothy Ravasi; Celia Schunter (Global Change Biology, 2022)
Ocean acidification (OA) is postulated to affect the physiology, behavior, and life‐history of marine species, but potential for acclimation or adaptation to elevated p CO 2 in wild populations remains largely untested. We measured brain transcriptomes of six coral reef fish species at a natural volcanic CO 2 seep and an adjacent control reef in Papua New Guinea. We show that elevated p CO 2 induced common molecular responses related to circadian rhythm and immune system but different magnitudes of molecular response across the six species. Notably, elevated transcriptional plasticity was associated with core circadian genes affecting the regulation of intracellular pH and neural activity in Acanthochromis polyacanthus . Gene expression patterns were reversible in this species as evidenced upon reduction of CO 2 following a natural storm‐event. Compared with other species, Ac . polyacanthus has a more rapid evolutionary rate and more positively selected genes in key functions under the influence of elevated CO 2 , thus fueling increased transcriptional plasticity. Our study reveals the basis to variable gene expression changes across species, with some species possessing evolved molecular toolkits to cope with future OA.

Ocean Futures for the World’s Largest Yellowfin Tuna Population Under the Combined Effects of Ocean Warming and Acidification - Simon Nicol; Patrick Lehodey; Inna Senina; Don Bromhead; Andrea Y. Frommel; John Hampton; Jon Havenhand; Daniel Margulies; Philip L. Munday; Vernon Scholey; Jane E. Williamson; Neville Smith (Frontiers in Marine Science, 2022)
The impacts of climate change are expected to have profound effects on the fisheries of the Pacific Ocean, including its tuna fisheries, the largest globally. This study examined the combined effects of climate change on the yellowfin tuna population using the ecosystem model SEAPODYM. Yellowfin tuna fisheries in the Pacific contribute significantly to the economies and food security of Pacific Island Countries and Territories and Oceania. We use an ensemble of earth climate models to project yellowfin populations under a high greenhouse gas emissions (IPCC RCP8.5) scenario, which includes, the combined effects of a warming ocean, increasing acidification and changing ocean chemistry. Our results suggest that the acidification impact will be smaller in comparison to the ocean warming impact, even in the most extreme ensemble member scenario explored, but will have additional influences on yellowfin tuna population dynamics. An eastward shift in the distribution of yellowfin tuna was observed in the projections in the model ensemble in the absence of explicitly accounting for changes in acidification. The extent of this shift did not substantially differ when the three-acidification induced larval mortality scenarios were included in the ensemble; however, acidification was projected to weaken the magnitude of the increase in abundance in the eastern Pacific. Together with intensive fishing, these potential changes are likely to challenge the global fishing industry as well as the economies and food systems of many small Pacific Island Countries and Territories. The modelling framework applied in this study provides a tool for evaluating such effects and informing policy development.

Molecular Response of the Brain to Cross-Generational Warming in a Coral Reef Fish - Moisés A. Bernal; Elliott Schmidt; Jennifer M. Donelson; Philip L. Munday; Timothy Ravasi (Frontiers in Marine Science, 2022)
Ocean warming is a threat to marine biodiversity, as it can push marine species beyond their physiological limits. Detrimental effects can occur when marine poikilotherms are exposed to conditions beyond their thermal optima. However, acclamatory mechanisms, such as plasticity, may enable compensation of detrimental effects if warming is experienced during development or across generations. Studies evaluating the molecular responses of fishes to warming have mostly focused on liver, muscle, and gonads, and little is known about the effects on other vital organs, including the brain. This study evaluated the transcriptional program of the brain in the coral reef fish Acanthochromis polyacanthus , exposed to two different warming scenarios: +1.5°C and +3.0°C, across successive generations. Fish were exposed to these conditions in both developmental (F1 and F2) and transgenerational settings (F2 only), as well as a treatment with step-wise warming between generations. The largest differences in gene expression were between individuals of the first and second generation, a pattern that was corroborated by pairwise comparisons between Control F1 and Control F2 (7,500 DEGs) fish. This large difference could be associated with parental effects, as parents of the F1 generation were collected from the wild, whereas parents of the F2 generation were reared in captivity. A general response to warming was observed at both temperatures and in developmental and transgenerational treatments included protein folding, oxygen transport (i.e., myoglobin), apoptosis and cell death, modification of cellular structure, mitochondrial activity, immunity and changes in circadian regulation. Treatments at the highest temperature showed a reduction in synaptic activity and neurotransmission, which matches previous behavioral observations in coral reef fishes. The Transgenerational +3.0°C treatment showed significant activation of the gene pls3 , which is known for the development of neuro-muscular junctions under heat-stress. F2 samples exposed to step-wise warming showed an intermediate response, with few differentially expressed genes compared to developmental and transgenerational groups (except for Transgenerational +1.5°C). In combination with previous studies on liver gene expression, this study indicates that warming produces a molecular signature of stress response in A. polyacanthus that is influenced both by the intensity of warming as well as the duration of exposure.

Diel p CO 2 fluctuations alter the molecular response of coral reef fishes to ocean acidification conditions - Celia Schunter; Michael D. Jarrold; Philip L. Munday; Timothy Ravasi (Molecular Ecology, 2021)
Environmental partial pressure of CO 2 ( p CO 2 ) variation can modify the responses of marine organisms to ocean acidification, yet the underlying mechanisms for this effect remain unclear. On coral reefs, environmental p CO 2 fluctuates on a regular day–night cycle. Effects of future ocean acidification on coral reef fishes might therefore depend on their response to this diel cycle of p CO 2 . To evaluate the effects on the brain molecular response, we exposed two common reef fishes ( Acanthochromis polyacanthus and Amphiprion percula ) to two projected future p CO 2 levels (750 and 1,000 µatm) under both stable and diel fluctuating conditions. We found a common signature to stable elevated p CO 2 for both species, which included the downregulation of immediate early genes, indicating lower brain activity. The transcriptional programme was more strongly affected by higher average p CO 2 in a stable treatment than for fluctuating treatments, but the largest difference in molecular response was between stable and fluctuating p CO 2 treatments. This indicates that a response to a change in environmental p CO 2 conditions is different for organisms living in a fluctuating than in stable environments. This differential regulation was related to steroid hormones and circadian rhythm (CR). Both species exhibited a marked difference in the expression of CR genes among p CO 2 treatments, possibly accommodating a more flexible adaptive approach in the response to environmental changes. Our results suggest that environmental p CO 2 fluctuations might enable reef fishes to phase‐shift their clocks and anticipate p CO 2 changes, thereby avoiding impairments and more successfully adjust to ocean acidification conditions.

Diel pCO2 variation among coral reefs and microhabitats at Lizard Island, Great Barrier Reef - Kelly D. Hannan; Gabrielle M. Miller; Sue-Ann Watson; Jodie L. Rummer; Katharina Fabricius; Philip L. Munday (Coral Reefs, 2020)

Proteomic Responses to Ocean Acidification in the Brain of Juvenile Coral Reef Fish - Hin Hung Tsang; Megan J. Welch; Philip L. Munday; Timothy Ravasi; Celia Schunter (Frontiers in Marine Science, 2020)

Toward a Mechanistic Understanding of Marine Invertebrate Behavior at Elevated CO2 - Jodi T. Thomas; Philip L. Munday; Sue-Ann Watson (Frontiers in Marine Science, 2020)

An Epigenetic Signature for Within-Generational Plasticity of a Reef Fish to Ocean Warming - Taewoo Ryu; Heather D. Veilleux; Philip L. Munday; Imgook Jung; Jennifer M. Donelson; Timothy Ravasi (Frontiers in Marine Science, 2020)

Elevated CO2 and heatwave conditions affect the aerobic and swimming performance of juvenile Australasian snapper - Shannon J. McMahon; Darren M. Parsons; Jennifer M. Donelson; Steve M. J. Pether; Philip L. Munday (Marine Biology, 2020)

Elevated Temperature Does Not Substantially Modify the Interactive Effects Between Elevated CO2 and Diel CO2 Cycles on the Survival, Growth and Behavior of a Coral Reef Fish - Michael D. Jarrold; Philip L. Munday (Frontiers in Marine Science, 2018)

Phenotypic and molecular consequences of stepwise temperature increase across generations in a coral reef fish - Moisés A. Bernal; Jennifer M. Donelson; Heather D. Veilleux; Taewoo Ryu; Philip L. Munday; Timothy Ravasi (Molecular Ecology, 2018)
Global warming will have far‐reaching consequences for marine species over coming decades, yet the magnitude of these effects may depend on the rate of warming across generations. Recent experiments show coral reef fishes can compensate the metabolic challenges of elevated temperature when warm conditions are maintained across generations. However, the effects of a gradual temperature increase across generations remain unknown. In the present study, we analysed metabolic and molecular traits in the damselfish Acanthochromis polyacanthus that were exposed to +1.5°C in the first generation and +3.0°C in the second (Step +3.0°C). This treatment of stepwise warming was compared to fish reared at current‐day temperatures (Control), second‐generation fish of control parents reared at +3.0°C (Developmental +3.0°C) and fish exposed to elevated temperatures for two generations (Transgenerational +1.5°C and Transgenerational +3.0°C). Hepatosomatic index, oxygen consumption and liver gene expression were compared in second‐generation fish of the multiple treatments. Hepatosomatic index increased in fish that developed at +3.0°C, regardless of the parental temperature. Routine oxygen consumption of Step +3.0°C fish was significantly higher than Control; however, their aerobic scope recovered to the same level as Control fish. Step +3.0°C fish exhibited significant upregulation of genes related to mitochondrial activity and energy production, which could be associated with their increased metabolic rates. These results indicate that restoration of aerobic scope is possible when fish experience gradual thermal increase across multiple generations, but the metabolic and molecular responses are different from fish reared at the same elevated thermal conditions in successive generations.

Molecular Response to Extreme Summer Temperatures Differs Between Two Genetically Differentiated Populations of a Coral Reef Fish - Heather D. Veilleux; Taewoo Ryu; Jennifer M. Donelson; Timothy Ravasi; Philip L. Munday (Frontiers in Marine Science, 2018)

Ocean warming has a greater effect than acidification on the early life history development and swimming performance of a large circumglobal pelagic fish - Sue‐Ann Watson; Bridie J. M. Allan; David E. McQueen; Simon Nicol; Darren M. Parsons; Stephen M. J. Pether; Stephen Pope; Alvin N. Setiawan; Neville Smith; Carly Wilson; Philip L. Munday (Global Change Biology, 2018)
Ocean warming and acidification are serious threats to marine life; however, their individual and combined effects on large pelagic and predatory fishes are poorly understood. We determined the effects of projected future temperature and carbon dioxide ( CO 2 ) levels on survival, growth, morphological development and swimming performance on the early life stages of a large circumglobal pelagic fish, the yellowtail kingfish Seriola lalandi . Eggs, larvae and juveniles were reared in cross‐factored treatments of temperature (21 and 25°C) and p CO 2 (500 and 985 μatm) from fertilisation to 25 days post hatching (dph). Temperature had the greatest effect on survival, growth and development. Survivorship was lower, but growth and morphological development were faster at 25°C, with surviving fish larger and more developed at 1, 11 and 21 dph. Elevated p CO 2 affected size at 1 dph, but not at 11 or 21 dph, and did not affect survival or morphological development. Elevated temperature and p CO 2 had opposing effects on swimming performance at 21 dph. Critical swimming speed ( U crit ) was increased by elevated temperature but reduced by elevated p CO 2 . Additionally, elevated temperature increased the proportion of individuals that responded to a startle stimulus, reduced latency to respond and increased maximum escape speed, potentially due to the more advanced developmental stage of juveniles at 25°C. By contrast, elevated p CO 2 reduced the distance moved and average speed in response to a startle stimulus. Our results show that higher temperature is likely to be the primary driver of global change impacts on kingfish early life history; however, elevated p CO 2 could affect critical aspects of swimming performance in this pelagic species. Our findings will help parameterise and structure fisheries population dynamics models and improve projections of impacts to large pelagic fishes under climate change scenarios to better inform adaptation and mitigation responses.

Predatory strategies and behaviours in cephalopods are altered by elevated CO 2 - Blake L. Spady; Philip L. Munday; Sue‐Ann Watson (Global Change Biology, 2018)
There is increasing evidence that projected near‐future carbon dioxide ( CO 2 ) levels can alter predator avoidance behaviour in marine invertebrates, yet little is known about the possible effects on predatory behaviours. Here we tested the effects of elevated CO 2 on the predatory behaviours of two ecologically distinct cephalopod species, the pygmy squid, Idiosepius pygmaeus , and the bigfin reef squid, Sepioteuthis lessoniana . Both species exhibited an increased latency to attack and altered body pattern choice during the attack sequence at elevated CO 2 . I. pygmaeus also exhibited a 20% decrease in predation rate, an increased striking distance, and reduced preference for attacking the posterior end of prey at elevated CO 2 . Elevated CO 2 increased activity levels of S. lessoniana comparable to those previously shown in I. pygmaeus , which could adversely affect their energy budget and increase their potential to be preyed upon. The effects of elevated CO 2 on predatory behaviours, predation strategies and activity levels of cephalopods reported here could have far‐reaching consequences in marine ecosystems due to the ecological importance of cephalopods in the marine food web.

Diel CO2 cycles do not modify juvenile growth, survival and otolith development in two coral reef fish under ocean acidification - Michael D. Jarrold; Philip L. Munday (Marine Biology, 2018)

Transgenerational plasticity and climate change experiments: Where do we go from here? - Jennifer M. Donelson; Santiago Salinas; Philip L. Munday; Lisa N. S. Shama (Global Change Biology, 2018)
Phenotypic plasticity, both within and across generations, is an important mechanism that organisms use to cope with rapid climate change. While an increasing number of studies show that plasticity across generations (transgenerational plasticity or TGP ) may occur, we have limited understanding of key aspects of TGP , such as the environmental conditions that may promote it, its relationship to within‐generation plasticity ( WGP ) and its role in evolutionary potential. In this review, we consider how the detection of TGP in climate change experiments is affected by the predictability of environmental variation, as well as the timing and magnitude of environmental change cues applied. We also discuss the need to design experiments that are able to distinguish TGP from selection and TGP from WGP in multigenerational experiments. We conclude by suggesting future research directions that build on the knowledge to date and admit the limitations that exist, which will depend on the way environmental change is simulated and the type of experimental design used. Such an approach will open up this burgeoning area of research to a wider variety of organisms and allow better predictive capacity of the role of TGP in the response of organisms to future climate change.

Effects of climate change on coral grouper (Plectropomus spp.) and possible adaptation options - Morgan S. Pratchett; Darren S. Cameron; Jennifer Donelson; Louisa Evans; Ashley J. Frisch; Alistair J. Hobday; Andrew S. Hoey; Nadine A. Marshall; Vanessa Messmer; Philip L. Munday; Rachel Pears; Gretta Pecl; et al. (Reviews in Fish Biology and Fisheries, 2017)

Depth distribution and abundance of a coral-associated reef fish: roles of recruitment and post-recruitment processes - Patrick F. Smallhorn-West; Tom C. L. Bridge; Philip L. Munday; Geoffrey P. Jones (Coral Reefs, 2017)

Potential for adaptation to climate change in a coral reef fish - Philip L. Munday; Jennifer M. Donelson; Jose A. Domingos (Global Change Biology, 2017)
Predicting the impacts of climate change requires knowledge of the potential to adapt to rising temperatures, which is unknown for most species. Adaptive potential may be especially important in tropical species that have narrow thermal ranges and live close to their thermal optimum. We used the animal model to estimate heritability, genotype by environment interactions and nongenetic maternal components of phenotypic variation in fitness‐related traits in the coral reef damselfish, Acanthochromis polyacanthus . Offspring of wild‐caught breeding pairs were reared for two generations at current‐day and two elevated temperature treatments (+1.5 and +3.0 °C) consistent with climate change projections. Length, weight, body condition and metabolic traits (resting and maximum metabolic rate and net aerobic scope) were measured at four stages of juvenile development. Additive genetic variation was low for length and weight at 0 and 15 days posthatching (dph), but increased significantly at 30 dph. By contrast, nongenetic maternal effects on length, weight and body condition were high at 0 and 15 dph and became weaker at 30 dph. Metabolic traits, including net aerobic scope, exhibited high heritability at 90 dph. Furthermore, significant genotype x environment interactions indicated potential for adaptation of maximum metabolic rate and net aerobic scope at higher temperatures. Net aerobic scope was negatively correlated with weight, indicating that any adaptation of metabolic traits at higher temperatures could be accompanied by a reduction in body size. Finally, estimated breeding values for metabolic traits in F2 offspring were significantly affected by the parental rearing environment. Breeding values at higher temperatures were highest for transgenerationally acclimated fish, suggesting a possible role for epigenetic mechanisms in adaptive responses of metabolic traits. These results indicate a high potential for adaptation of aerobic scope to higher temperatures, which could enable reef fish populations to maintain their performance as ocean temperatures rise.

Climate change and the evolution of reef fishes: past and future - Jodie L Rummer; Philip L Munday (Fish and Fisheries, 2017)
Predicting the impacts of ocean warming and acidification on marine ecosystems requires an evolutionary perspective because, for most marine species, these environmental changes will occur over a number of generations. Acclimation through phenotypic plasticity and adaptation through genetic selection could help populations of some species cope with future warmer and more acidic oceans. Coral reef species are predicted to be some of the most vulnerable to climate change because they live close to their thermal limits. Yet, their evolutionary history may indicate that they possess adaptations that enable them to cope with a high CO 2 environment. Here, we first explore the evolutionary history of reef fishes and how their history has shaped their physiological adaptations to environmental temperatures and pCO 2 . We examine current‐day thermal and CO 2 environments experienced by coral reef fishes and summarize experimental studies that have tested how they respond to elevated temperatures and pCO 2 levels. We then examine evidence for acclimation and adaptation to projected ocean warming and acidification. Indeed, new studies have demonstrated the potential for transgenerational plasticity and heritable genetic variation that would allow some fishes to maintain performance as the oceans warm and become more acidic. We conclude by outlining management approaches – specifically those that can help preserve genetic variation by maintaining population size – to enhance the potential for genetic adaptation to climate change.

Near‐future pH conditions severely impact calcification, metabolism and the nervous system in the pteropod Heliconoides inflatus - Aurelie Moya; Ella L. Howes; Thomas Lacoue‐Labarthe; Sylvain Forêt; Bishoy Hanna; Mónica Medina; Philip L. Munday; Jue‐Sheng Ong; Jean‐Louis Teyssié; Gergely Torda; Sue‐Ann Watson; David J. Miller; et al. (Global Change Biology, 2016)
Shelled pteropods play key roles in the global carbon cycle and food webs of various ecosystems. Their thin external shell is sensitive to small changes in pH, and shell dissolution has already been observed in areas where aragonite saturation state is ~1. A decline in pteropod abundance has the potential to disrupt trophic networks and directly impact commercial fisheries. Therefore, it is crucial to understand how pteropods will be affected by global environmental change, particularly ocean acidification. In this study, physiological and molecular approaches were used to investigate the response of the Mediterranean pteropod, Heliconoides inflatus , to pH values projected for 2100 under a moderate emissions trajectory ( RCP 6.0). Pteropods were subjected to pH T 7.9 for 3 days, and gene expression levels, calcification and respiration rates were measured relative to pH T 8.1 controls. Gross calcification decreased markedly under low pH conditions, while genes potentially involved in calcification were up‐regulated, reflecting the inability of pteropods to maintain calcification rates. Gene expression data imply that under low pH conditions, both metabolic processes and protein synthesis may be compromised, while genes involved in acid–base regulation were up‐regulated. A large number of genes related to nervous system structure and function were also up‐regulated in the low pH treatment, including a GABA A receptor subunit. This observation is particularly interesting because GABA A receptor disturbances, leading to altered behavior, have been documented in several other marine animals after exposure to elevated CO 2 . The up‐regulation of many genes involved in nervous system function suggests that exposure to low pH could have major effects on pteropod behavior. This study illustrates the power of combining physiological and molecular approaches. It also reveals the importance of behavioral analyses in studies aimed at understanding the impacts of low pH on marine animals.

Erratum to: Contrasting effects of ocean acidification on reproduction in reef fishes - Megan J. Welch; Philip L. Munday (Coral Reefs, 2016)

Contrasting effects of ocean acidification on reproduction in reef fishes - Megan J. Welch; Philip L. Munday (Coral Reefs, 2016)

Animal behaviour shapes the ecological effects of ocean acidification and warming: moving from individual to community‐level responses - Ivan Nagelkerken; Philip L. Munday (Global Change Biology, 2016)
Biological communities are shaped by complex interactions between organisms and their environment as well as interactions with other species. Humans are rapidly changing the marine environment through increasing greenhouse gas emissions, resulting in ocean warming and acidification. The first response by animals to environmental change is predominantly through modification of their behaviour, which in turn affects species interactions and ecological processes. Yet, many climate change studies ignore animal behaviour. Furthermore, our current knowledge of how global change alters animal behaviour is mostly restricted to single species, life phases and stressors, leading to an incomplete view of how coinciding climate stressors can affect the ecological interactions that structure biological communities. Here, we first review studies on the effects of warming and acidification on the behaviour of marine animals. We demonstrate how pervasive the effects of global change are on a wide range of critical behaviours that determine the persistence of species and their success in ecological communities. We then evaluate several approaches to studying the ecological effects of warming and acidification, and identify knowledge gaps that need to be filled, to better understand how global change will affect marine populations and communities through altered animal behaviours. Our review provides a synthesis of the far‐reaching consequences that behavioural changes could have for marine ecosystems in a rapidly changing environment. Without considering the pervasive effects of climate change on animal behaviour we will limit our ability to forecast the impacts of ocean change and provide insights that can aid management strategies.

Competitive mechanisms change with ontogeny in coral‐dwelling gobies - Pedro H. Cipresso Pereira; Philip L. Munday; Geoffrey P. Jones (Ecology, 2015)
Recent theory suggests that a mix of lottery and niche processes can facilitate coexistence between competing species, but this has not yet been empirically tested. Previous research has suggested that a competitive lottery for space promotes coexistence between two ecologically similar species, Gobiodon histrio and Gobiodon erythrospilus . However, not all the assumptions of lottery competition have been tested, and patterns of habitat use by adults suggest niche partitioning. Here, we investigated the hypothesis that the mechanism of competition changes with ontogeny, with a lottery for space operating at settlement and niche partitioning occurring in adults. Patterns of resource use in the field were compared for juveniles and adults of the two species. Pelagic larval duration (PLD) and size‐at‐settlement was also estimated to determine if size differences at settlement could affect the outcome of competitive interactions among juveniles. Habitat preference and size‐based competitive ability were then tested for juveniles and adults in laboratory experiments. Finally, a transplant experiment was performed to test the fitness‐associated consequences of niche partitioning among adults and its implications for coexistence of the two species. G. histrio had a similar PLD (20.7 ± 2.0 days) to G. erythrospilus (18.5 ± 1.9 days), and there was no difference in size‐at‐settlement between the species. Juveniles of the two species had similar patterns of habitat use and similar competitive abilities, supporting the lottery mechanism at settlement. However, adults differ in their habitat use, supporting the prediction that resource partitioning increases with ontogeny. In laboratory experiments, adults of each species preferred colonies of Acropora nasuta . However, G. histrio was a superior competitor and prevented G. erythrospilus from using A. nasuta in >70% of the trials. In the field transplant experiment, G. erythrospilus (inferior competitor) suffered less of a fitness loss when occupying the non‐preferred coral ( A. spathulata ) compared with G. histrio , which could explain its ability to persist when displaced by the superior competitor. These results suggest that the competitive mechanism operating between the two Gobiodon species shifts from a lottery for space to niche partitioning through ontogeny, and that these two mechanisms of competitive coexistence are not mutually exclusive.

Transgenerational plasticity mitigates the impact of global warming to offspring sex ratios - Jennifer M. Donelson; Philip L. Munday (Global Change Biology, 2015)
Global warming poses a threat to organisms with temperature‐dependent sex determination because it can affect operational sex ratios. Using a multigenerational experiment with a marine fish, we provide the first evidence that parents developing from early life at elevated temperatures can adjust their offspring gender through nongenetic and nonbehavioural means. However, this adjustment was not possible when parents reproduced, but did not develop, at elevated temperatures. Complete restoration of the offspring sex ratio occurred when parents developed at 1.5 °C above the present‐day average temperature for one generation. However, only partial improvement in the sex ratio occurred at 3.0 °C above average conditions, even after two generations, suggesting a limitation to transgenerational plasticity when developmental temperature is substantially increased. This study highlights the potential for transgenerational plasticity to ameliorate some impacts of climate change and that development from early life may be essential for expression of transgenerational plasticity in some traits.

Interactive effects of ocean acidification and rising sea temperatures alter predation rate and predator selectivity in reef fish communities - Maud. C. O. Ferrari; Philip L. Munday; Jodie L. Rummer; Mark I. McCormick; Katherine Corkill; Sue‐Ann Watson; Bridie J. M. Allan; Mark G. Meekan; Douglas P. Chivers (Global Change Biology, 2015)
Ocean warming and acidification are serious threats to marine life. While each stressor alone has been studied in detail, their combined effects on the outcome of ecological interactions are poorly understood. We measured predation rates and predator selectivity of two closely related species of damselfish exposed to a predatory dottyback. We found temperature and CO 2 interacted synergistically on overall predation rate, but antagonistically on predator selectivity. Notably, elevated CO 2 or temperature alone reversed predator selectivity, but the interaction between the two stressors cancelled selectivity. Routine metabolic rates of the two prey showed strong species differences in tolerance to CO 2 and not temperature, but these differences did not correlate with recorded mortality. This highlights the difficulty of linking species‐level physiological tolerance to resulting ecological outcomes. This study is the first to document both synergistic and antagonistic effects of elevated CO 2 and temperature on a crucial ecological process like predator–prey dynamics.

Odor tracking in sharks is reduced under future ocean acidification conditions - Danielle L. Dixson; Ashley R. Jennings; Jelle Atema; Philip L. Munday (Global Change Biology, 2015)
Recent studies show that ocean acidification impairs sensory functions and alters the behavior of teleost fishes. If sharks and other elasmobranchs are similarly affected, this could have significant consequences for marine ecosystems globally. Here, we show that projected future CO 2 levels impair odor tracking behavior of the smooth dogfish ( Mustelus canis ). Adult M. canis were held for 5 days in a current‐day control (405 ± 26 μatm) and mid (741 ± 22 μatm) or high CO 2 (1064 ± 17 μatm) treatments consistent with the projections for the year 2100 on a ‘business as usual’ scenario. Both control and mid CO 2 ‐treated individuals maintained normal odor tracking behavior, whereas high CO 2 ‐treated sharks significantly avoided the odor cues indicative of food. Control sharks spent >60% of their time in the water stream containing the food stimulus, but this value fell below 15% in high CO 2 ‐treated sharks. In addition, sharks treated under mid and high CO 2 conditions reduced attack behavior compared to the control individuals. Our findings show that shark feeding could be affected by changes in seawater chemistry projected for the end of this century. Understanding the effects of ocean acidification on critical behaviors, such as prey tracking in large predators, can help determine the potential impacts of future ocean acidification on ecosystem function.

Ocean acidification through the lens of ecological theory - Brian Gaylord; Kristy J. Kroeker; Jennifer M. Sunday; Kathryn M. Anderson; James P. Barry; Norah E. Brown; Sean D Connell; Sam Dupont; Katharina E. Fabricius; Jason M. Hall-Spencer; Terrie Klinger; Marco Milazzo; et al. (Ecology, 2015)
Ocean acidification, chemical changes to the carbonate system of seawater, is emerging as a key environmental challenge accompanying global warming and other human‐induced perturbations. Considerable research seeks to define the scope and character of potential outcomes from this phenomenon, but a crucial impediment persists. Ecological theory, despite its power and utility, has been only peripherally applied to the problem. Here we sketch in broad strokes several areas where fundamental principles of ecology have the capacity to generate insight into ocean acidification's consequences. We focus on conceptual models that, when considered in the context of acidification, yield explicit predictions regarding a spectrum of population‐ and community‐level effects, from narrowing of species ranges and shifts in patterns of demographic connectivity, to modified consumer–resource relationships, to ascendance of weedy taxa and loss of species diversity. Although our coverage represents only a small fraction of the breadth of possible insights achievable from the application of theory, our hope is that this initial foray will spur expanded efforts to blend experiments with theoretical approaches. The result promises to be a deeper and more nuanced understanding of ocean acidification and the ecological changes it portends.

Habitat degradation modifies the strength of interspecific competition in coral dwelling damselfishes - Lisa Boström-Einarsson; Mary C. Bonin; Philip L. Munday; Geoffrey P. Jones (Ecology, 2014)
Habitat degradation is predicted to exacerbate competition for critical resources; however, the relationship between habitat quality and competition is poorly understood. In this study, we used a manipulative experiment to test the effects of habitat degradation on competition between two planktivorous, coral‐dwelling damselfishes, Chrysiptera parasema and Dascyllus melanurus . Experimental reefs were constructed with either healthy (100% live) or degraded (10% live) Acropora longicyathus coral, stocked with varying densities of these two fish species, and monitored for two months. On healthy habitat, the mortality of C. parasema was density dependent, and increased substantially in the presence of the dominant interspecific competitor D. melanurus . In contrast, on reefs where habitat was degraded, C. parasema mortality was highly variable, density independent, and was no longer influenced by the presence of dominant competitor D. melanurus . Behavioral observations revealed that agonistic interactions for both species increased with density on degraded habitat, but not on healthy habitat. In addition, on degraded reefs, both species displayed a reduced association with reef habitat and ventured further away from shelter with increasing densities of the dominant competitor D. melanurus . These results suggest that reduced habitat quality can have such a profound effect on reef fishes, that it eliminates density‐dependent mortality and competitive dominance hierarchies, thereby substantially altering the mechanisms that structure reef fish communities.

Experimental evaluation of diversity–productivity relationships in a coral reef fish assemblage - Vanessa Messmer; Shane A. Blowes; Geoffrey P. Jones; Philip L. Munday (Oecologia, 2014)

Life on the edge: thermal optima for aerobic scope of equatorial reef fishes are close to current day temperatures - Jodie L. Rummer; Christine S. Couturier; Jonathan A. W. Stecyk; Naomi M. Gardiner; Jeff P. Kinch; Göran E. Nilsson; Philip L. Munday (Global Change Biology, 2014)
Equatorial populations of marine species are predicted to be most impacted by global warming because they could be adapted to a narrow range of temperatures in their local environment. We investigated the thermal range at which aerobic metabolic performance is optimum in equatorial populations of coral reef fish in northern Papua New Guinea. Four species of damselfishes and two species of cardinal fishes were held for 14 days at 29, 31, 33, and 34 °C, which incorporated their existing thermal range (29–31 °C) as well as projected increases in ocean surface temperatures of up to 3 °C by the end of this century. Resting and maximum oxygen consumption rates were measured for each species at each temperature and used to calculate the thermal reaction norm of aerobic scope. Our results indicate that one of the six species, Chromis atripectoralis , is already living above its thermal optimum of 29 °C. The other five species appeared to be living close to their thermal optima (ca. 31 °C). Aerobic scope was significantly reduced in all species, and approached zero for two species at 3 °C above current‐day temperatures. One species was unable to survive even short‐term exposure to 34 °C. Our results indicate that low‐latitude reef fish populations are living close to their thermal optima and may be more sensitive to ocean warming than higher‐latitude populations. Even relatively small temperature increases (2–3 °C) could result in population declines and potentially redistribution of equatorial species to higher latitudes if adaptation cannot keep pace.

Aerobic vs. anaerobic scope: sibling species of fish indicate that temperature dependence of hypoxia tolerance can predict future survival - Christina Sørensen; Philip L. Munday; Göran E. Nilsson (Global Change Biology, 2014)
The temperature dependence of aerobic scope has been suggested to be a major determinant of how marine animals will cope with future rises in environmental temperature. Here, we present data suggesting that in some animals, the temperature dependence of anaerobic scope (i.e., the capacity for surviving severe hypoxia) may determine present‐day latitudinal distributions and potential for persistence in a warmer future. As a model for investigating the role of anaerobic scope, we studied two sibling species of coral‐dwelling gobies, Gobiodon histrio, and G. erythrospilus , with different latitudinal distributions, but which overlap in equal abundance at Lizard Island (14°40′S) on the Great Barrier Reef. These species did not differ in the temperature dependence of resting oxygen consumption or critical oxygen concentration (the lowest oxygen level where resting oxygen consumption can be maintained). In contrast, the more equatorial species ( G. histrio ) had a better capacity to endure anaerobic conditions at oxygen levels below the critical oxygen concentration at the high temperatures (32–33 °C) more likely to occur near the equator, or in a warmer future. These results suggest that anaerobic scope, in addition to aerobic scope, could be important in determining the impacts of global warming on some marine animals.

Impaired learning of predators and lower prey survival under elevated CO 2 : a consequence of neurotransmitter interference - Douglas P. Chivers; Mark I. McCormick; Göran E. Nilsson; Philip L. Munday; Sue‐Ann Watson; Mark G. Meekan; Matthew D. Mitchell; Katherine C. Corkill; Maud C. O. Ferrari (Global Change Biology, 2014)
Ocean acidification is one of the most pressing environmental concerns of our time, and not surprisingly, we have seen a recent explosion of research into the physiological impacts and ecological consequences of changes in ocean chemistry. We are gaining considerable insights from this work, but further advances require greater integration across disciplines. Here, we showed that projected near‐future CO 2 levels impaired the ability of damselfish to learn the identity of predators. These effects stem from impaired neurotransmitter function; impaired learning under elevated CO 2 was reversed when fish were treated with gabazine, an antagonist of the GABA ‐A receptor – a major inhibitory neurotransmitter receptor in the brain of vertebrates. The effects of CO 2 on learning and the link to neurotransmitter interference were manifested as major differences in survival for fish released into the wild. Lower survival under elevated CO 2 , as a result of impaired learning, could have a major influence on population recruitment.

Experimental evaluation of imprinting and the role innate preference plays in habitat selection in a coral reef fish - Danielle L. Dixson; Geoffrey P. Jones; Philip L. Munday; Serge Planes; Morgan S. Pratchett; Simon R. Thorrold (Oecologia, 2014)

Predicting evolutionary responses to climate change in the sea - Philip L. Munday; Robert R. Warner; Keyne Monro; John M. Pandolfi; Dustin J. Marshall (Ecology Letters, 2013)
An increasing number of short‐term experimental studies show significant effects of projected ocean warming and ocean acidification on the performance on marine organisms. Yet, it remains unclear if we can reliably predict the impact of climate change on marine populations and ecosystems, because we lack sufficient understanding of the capacity for marine organisms to adapt to rapid climate change. In this review, we emphasise why an evolutionary perspective is crucial to understanding climate change impacts in the sea and examine the approaches that may be useful for addressing this challenge. We first consider what the geological record and present‐day analogues of future climate conditions can tell us about the potential for adaptation to climate change. We also examine evidence that phenotypic plasticity may assist marine species to persist in a rapidly changing climate. We then outline the various experimental approaches that can be used to estimate evolutionary potential, focusing on molecular tools, quantitative genetics, and experimental evolution, and we describe the benefits of combining different approaches to gain a deeper understanding of evolutionary potential. Our goal is to provide a platform for future research addressing the evolutionary potential for marine organisms to cope with climate change.

Increased CO 2 stimulates reproduction in a coral reef fish - Gabrielle M. Miller; Sue‐Ann Watson; Mark I. McCormick; Philip L. Munday (Global Change Biology, 2013)
Ocean acidification is predicted to negatively impact the reproduction of many marine species, either by reducing fertilization success or diverting energy from reproductive effort. While recent studies have demonstrated how ocean acidification will affect larval and juvenile fishes, little is known about how increasing partial pressure of carbon dioxide ( p CO 2 ) and decreasing pH might affect reproduction in adult fishes. We investigated the effects of near‐future levels of p CO 2 on the reproductive performance of the cinnamon anemonefish, A mphiprion melanopus , from the G reat B arrier R eef, A ustralia. Breeding pairs were held under three CO 2 treatments [Current‐day Control (430 μatm), Moderate (584 μatm) and High (1032 μatm)] for a 9‐month period that included the summer breeding season. Unexpectedly, increased CO 2 dramatically stimulated breeding activity in this species of fish. Over twice as many pairs bred in the Moderate (67% of pairs) and High (55%) compared to the Control (27%) CO 2 treatment. Pairs in the High CO 2 group produced double the number of clutches per pair and 67% more eggs per clutch compared to the Moderate and Control groups. As a result, reproductive output in the High group was 82% higher than that in the Control group and 50% higher than that in the Moderate group. Despite the increase in reproductive activity, there was no difference in adult body condition among the three treatment groups. There was no significant difference in hatchling length between the treatment groups, but larvae from the High CO 2 group had smaller yolks than Controls. This study provides the first evidence of the potential effects of ocean acidification on key reproductive attributes of marine fishes and, contrary to expectations, demonstrates an initially stimulatory (hormetic) effect in response to increased p CO 2 . However, any long‐term consequences of increased reproductive effort on individuals or populations remain to be determined.

Elevated CO2 affects the behavior of an ecologically and economically important coral reef fish - Philip L. Munday; Morgan S. Pratchett; Danielle L. Dixson; Jennifer M. Donelson; Geoff G. K. Endo; Adam D. Reynolds; Richard Knuckey (Marine Biology, 2013)

Habitat preferences of coral-associated fishes are altered by short-term exposure to elevated CO2 - Brynn M. Devine; Philip L. Munday (Marine Biology, 2013)

Towards improved socio-economic assessments of ocean acidification’s impacts - Nathalie Hilmi; Denis Allemand; Sam Dupont; Alain Safa; Gunnar Haraldsson; Paulo A. L. D. Nunes; Chris Moore; Caroline Hattam; Stéphanie Reynaud; Jason M. Hall-Spencer; Maoz Fine; Carol Turley; et al. (Marine Biology, 2013)

Prey selectivity affects reproductive success of a corallivorous reef fish - Rohan M. Brooker; Geoffrey P. Jones; Philip L. Munday (Oecologia, 2013)

Homing ability of adult cardinalfish is affected by elevated carbon dioxide - Brynn M. Devine; Philip L. Munday; Geoffrey P. Jones (Oecologia, 2012)

Biogeography and the structure of coral reef fish communities on isolated islands - Jean‐Paul A. Hobbs; Geoffrey P. Jones; Philip L. Munday; Sean R. Connolly; Maya Srinivasan (Journal of Biogeography, 2012)
Aim To determine the applicability of biogeographical and ecological theory to marine species at two remote island locations. This study examines how biogeography, isolation and species geographic range size influence patterns of species richness, endemism, species composition and the abundance of coral reef fishes. Location Christmas Island and the Cocos (Keeling) Islands in the tropical eastern Indian Ocean. Methods Published species lists and underwater visual surveys were used to determine species richness, endemism, species composition and abundance of reef fishes at the islands. These data were statistically compared with patterns of species composition and abundance from the neighbouring ‘mainland’ Indonesian region. Results The two isolated reef fish communities were species‐poor and contained a distinct taxonomic composition with an overrepresentation of species with high dispersal potential. Despite low species richness, we found no evidence of density compensation, with population densities on the islands similar to those of species‐rich mainland assemblages. The mix of Indian and Pacific Ocean species and the proportional representations of the various regional faunas in the assemblages were not influenced by the relative proximity of the islands to different biogeographical provinces. Moreover, species at the edge of their range did not have a lower abundance than species at the centre of their range, and endemic species had substantially higher abundances than widespread species. At both locations, endemism was low (less than 1.2% of the community); this may be because the locations are not sufficiently isolated or old enough to promote the evolution of endemic species. Main conclusions The patterns observed generally conform to terrestrial biogeographical theory, suggesting that similar processes may be influencing species richness and community composition in reef fish communities at these remote islands. However, species abundances differed from typical terrestrial patterns, and this may be because of the life history of reef fishes and the processes maintaining isolated populations.

Intrageneric variation in antipredator responses of coral reef fishes affected by ocean acidification: implications for climate change projections on marine communities - MAUD C. O. FERRARI; DANIELLE L. DIXSON; PHILIP L. MUNDAY; MARK I. McCORMICK; MARK G. MEEKAN; ANDREW SIH; DOUGLAS P. CHIVERS (Global Change Biology, 2011)
Our planet is experiencing an increase in the concentration of atmospheric carbon dioxide (CO 2 ) unprecedented in the past 800 000 years. About 30% of excess atmospheric CO 2 is absorbed by the oceans, thus increasing the concentration of carbonic acid and reducing the ocean's pH. Species able to survive the physiological stress imposed by ocean acidification may still suffer strong indirect negative consequences. Comparing the tolerance of different species to dissolved CO 2 is a necessary first step towards predicting the ecological impacts of rising CO 2 levels on marine communities. While it is intuitive that not all aquatic species will be affected the same way by CO 2 , one could predict that closely related species, sharing similar life histories and ecology, may show similar tolerance levels to CO 2 . Our ability to create functional groups of species according to their CO 2 tolerance may be crucial in our ability to predict community change in the future. Here, we tested the effects of CO 2 exposure on the antipredator responses of four damselfish species ( Pomacentrus chrysurus, Pomacentrus moluccensis, Pomacentrus amboinensis and Pomacentrus nagasakiensis ). Although being sympatric and sharing the same ecology and life history, the four congeneric species showed striking and unexpected variation in CO 2 tolerance, with CO 2 ‐induced loss of response to predation risk ranging from 30% to 95%. Using P. chrysurus as a model species, we further tested if these behavioural differences translated into differential ability to survive predators under natural conditions. Our results indicate that P. chrysurus larvae raised under CO 2 levels predicted by 2070 and 2100 showed decreased antipredator responses to risk, leading to a five‐ to sevenfold increase in predation‐related mortality in the first few hours of settlement. Examining ocean acidification, along with other environmental variables, will be a critical step in further evaluating ecological responses to predicted climatic change.

RETRACTED: Ocean acidification disrupts the innate ability of fish to detect predator olfactory cues - Danielle L. Dixson; Philip L. Munday; Geoffrey P. Jones (Ecology Letters, 2010)
While ocean acidification is predicted to threaten marine biodiversity, the processes that directly impact species persistence are not well understood. For marine species, early life history stages are inherently vulnerable to predators and an innate ability to detect predators can be critical for survival. However, whether or not acidification inhibits predator detection is unknown. Here, we show that newly hatched larvae of the marine fish Amphiprion percula innately detect predators using olfactory cues and this ability is retained through to settlement. Aquarium‐reared larvae, not previously exposed to predators, were able to distinguish between the olfactory cues of predatory and non‐predatory species. However, when eggs and larvae were exposed to seawater simulating ocean acidification (pH 7.8 and 1000 p.p.m. CO 2 ) settlement‐stage larvae became strongly attracted to the smell of predators and the ability to discriminate between predators and non‐predators was lost. Newly hatched larvae were unaffected by CO 2 exposure and were still able to distinguish between predatory and non‐predatory fish. If this impairment of olfactory preferences in settlement‐stage larvae translates to higher mortality as a result of increased predation risk, there could be direct consequences for the replenishment and the sustainability of marine populations. Ecology Letters (2010) 13: 68–75

Elevated temperature reduces the respiratory scope of coral reef fishes - GÖRAN E. NILSSON; NATALIE CRAWLEY; IDA G. LUNDE; PHILIP L. MUNDAY (Global Change Biology, 2009)
The capacity for marine fishes to perform aerobically (aerobic scope) is predicted to control their thermal tolerance and, thus, the impact that rapid climate change will have on their populations. We tested the effect of increased water temperatures on the resting and maximum rates of oxygen consumption in five common coral reef fishes at Lizard Island on the northern Great Barrier Reef, Australia. All species exhibited a decline in aerobic capacity at elevated water temperatures (31, 32 or 33 °C) compared with controls (29 °C); however, the response was much stronger in two cardinalfishes, Ostorhinchus cyanosoma and O. doederleini , compared with three damselfishes, Dascyllus anuarus, Chromis atripectoralis and Acanthochromis polyacanthus . Aerobic scope of the two cardinalfishes was reduced by nearly half at 31 °C compared with 29 °C, and virtually all capacity for additional oxygen uptake was exhausted by 33 °C. In contrast, the three damselfishes retained over half their aerobic scope at 33 °C. Such differences in thermal tolerance between species, and possibly families, suggest that the community structure of reef fish assemblages might change significantly as ocean temperatures increase. Populations of thermally tolerant species are likely to persist at higher temperatures, but populations of thermally sensitive species could decline on low‐latitude reefs if individual performance falls below levels needed to sustain viable populations.

Climate change and the future for coral reef fishes - Philip L Munday; Geoffrey P Jones; Morgan S Pratchett; Ashley J Williams (Fish and Fisheries, 2008)
Climate change will impact coral‐reef fishes through effects on individual performance, trophic linkages, recruitment dynamics, population connectivity and other ecosystem processes. The most immediate impacts will be a loss of diversity and changes to fish community composition as a result of coral bleaching. Coral‐dependent fishes suffer the most rapid population declines as coral is lost; however, many other species will exhibit long‐term declines due to loss of settlement habitat and erosion of habitat structural complexity. Increased ocean temperature will affect the physiological performance and behaviour of coral reef fishes, especially during their early life history. Small temperature increases might favour larval development, but this could be counteracted by negative effects on adult reproduction. Already variable recruitment will become even more unpredictable. This will make optimal harvest strategies for coral reef fisheries more difficult to determine and populations more susceptible to overfishing. A substantial number of species could exhibit range shifts, with implications for extinction risk of small‐range species near the margins of reef development. There are critical gaps in our knowledge of how climate change will affect tropical marine fishes. Predictions are often based on temperate examples, which may be inappropriate for tropical species. Improved projections of how ocean currents and primary productivity will change are needed to better predict how reef fish population dynamics and connectivity patterns will change. Finally, the potential for adaptation to climate change needs more attention. Many coral reef fishes have geographical ranges spanning a wide temperature gradient and some have short generation times. These characteristics are conducive to acclimation or local adaptation to climate change and provide hope that the more resilient species will persist if immediate action is taken to stabilize Earth’s climate.

Phylogeography of colour polymorphism in the coral reef fish Pseudochromis fuscus, from Papua New Guinea and the Great Barrier Reef - Vanessa Messmer; Lynne van Herwerden; Philip L. Munday; Geoffrey P. Jones (Coral Reefs, 2005)

Genetic and Ecological Characterisation of Colour Dimorphism in a Coral Reef Fish - Vanessa Messmer; Geoffrey P. Jones; Lynne van Herwerden; Philip L. Munday (Environmental Biology of Fishes, 2005)

Habitat Patch Size, Facultative Monogamy and Sex Change in a Coral-dwelling Fish, Caracanthus unipinna - Marian Y.L. Wong; Philip L. Munday; Geoffrey P. Jones (Environmental Biology of Fishes, 2005)

Habitat loss, resource specialization, and extinction on coral reefs - Philip L. Munday (Global Change Biology, 2004)
Coral reefs worldwide are being degraded because of global warming (coral bleaching) and coastal development (sedimentation and eutrophication). Predicting the risk of species extinctions from this type of habitat degradation is one of the most challenging and urgent tasks facing ecologists. Habitat specialists are thought to be more prone to extinction than generalists; however, specialists may be more susceptible to extinction because (1) they are specialists per se , (2) they are less abundant than generalists, or (3) both. Here, I show that declines in coral abundance lead to corresponding declines in the abundance of coral‐dwelling fishes, but with proportionally greater losses to specialists than generalists. In addition, specialists have smaller initial population sizes than generalists. Consequently, specialists face a dual risk of extinction because their already small populations decline more rapidly than those of generalists. Corresponding with this increased extinction risk, I describe the local extinction of one specialist species and the near‐global extinction of another species. I conclude that habitat specialists will be the first species lost from coral reefs because their small populations suffer the most from human‐induced disturbances.

Ecological mechanisms for coexistence of colour polymorphism in a coral-reef fish: an experimental evaluation - Philip L. Munday; Peter J. Eyre; Geoffrey P. Jones (Oecologia, 2003)

The Toxicity of Skin Secretions from Coral-Dwelling Gobies and their Potential Role as a Predator Deterrent - Melissa Schubert; Philip L. Munday; M. Julian Caley; Geoffrey P. Jones; Lyndon E. Llewellyn (Environmental Biology of Fishes, 2003)

Fitness consequences of habitat use and competition among coral-dwelling fishes - Philip L. Munday (Oecologia, 2001)

Interactions Between Habitat Use and Patterns of Abundance in Coral-dwelling Fishes of the Genus Gobiodon - Philip L. Munday (Environmental Biology of Fishes, 2000)

Bi-directional sex change in a coral-dwelling goby - Philip L. Munday; M. Julian Caley; Geoffrey P. Jones (Behavioral Ecology and Sociobiology, 1998)